Characteristics of Hydro-Oceanography in the Coastal Waters of Kura-Kura Beach, Bengkayang Regency - Muhardi Muhardi; Risko Risko; Heni Susiati (JIPF (Jurnal Ilmu Pendidikan Fisika), 2021)
The waters of Kura-Kura Beach have quite a lot of human activities, one of which is tourism. The study aims to observe Hydro-Oceanographic parameters such as tidal conditions, ocean currents, and waves. The study uses field observation data and simulation results. The data is calculated to find Formzhal number based on the amplitude of tidal harmonic constants. The Flow analysis to determine the pattern and velocity of the current. The height and period of the wave to analyze characteristics of the wave. The results show that the tide in Kura-Kura Beach waters is a daily mix of a double with the highest tide at MSL and a minimum tide of 0.43 below MSL. While the current velocity obtained from the yield model has a range of (0.003 - 0.11) m/s, and the measurement results are between (0.005 - 0.14) m/s. The simulation results show that the current moves from land to sea at low tide, and it moves from sea to land at toward the tide. For the height of the ocean waves that are formed in a period of 10 years (2009 - 2019) ranges from (0.09 - 154) m and the wave period (1.86 - 5.73) seconds. Based on the calculation results, the largest wave energy occurs in the second intermediate period, namely 184.21 Joules/m with height and wave periods of 1.21 m and 4.39 seconds. In contrast, the smallest wave energy occurs in the first intermediate period with minimum wave height and period 0.18 m and 3.08 seconds. In general, based on the simulation of the current velocity model, the forecasting of wave height and wave energy in Kura-Kura Beach waters is still relatively small. So, it can be concluded that the location is still categorized as safe for coastal tourism and other activities.